Penanaman Perilaku Hidup Bersih Dan Sehat (PHBS) Oleh Orang Tua Muslim Kepada Anak Usia Dini Saat Wabah COVID-19 - Yayah Rukhiyah; Busthomi Ibrohim; Nila Karunia (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2022)
This study is intended to understand how parents of early childhood instill clean and healthy living behavior (PHBS) in them in urban village areas during the COVID-19 pandemic. By allowing conditions to run naturally, the use of a qualitative methodology with an ethnographic pattern is the choice in this research method. All informants are devoted to families who have children aged 5 years who experience school from home by collecting data through observation, documentation and in-depth interviews. As a result, PHBS education has been carried out by parents according to the abilities and conditions of each family. These limitations cause certain behaviors that occur during a pandemic that do not run optimally, such as the use of masks. Suggestions for further studies are research on PHBS education which involves three educational environments for early childhood, both during the pandemic or normal.